BUSINESS CAPITAL IN BTPN SHARIA BRANCH LHOKSUKON DISTRIBUTION: IN THE ISLAMIC ECONOMIC ETHICS PERSPECTIVE - Taufiq; Yoesrizal M. Yoesoef; Miftahul Husna (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
This study aims to analyze the business capital distribution system by National Pension Savings Bank (BTPN) Sharia Lhoksukon Branch Office which is focused on women in the Lhoksukon village, North Aceh. This research is qualitative research with descriptive analysis approach which is a field study (Field Research). Data sourced from primary data and secondary data. The results show that the capital distribution mechanism is in accordance with the distribution procedures carried out by Islamic Financial Institutions (LKS) in general. However, in practice there are still deviations that occur where National Pension Savings Bank (BTPN) Sharia is still implementing a revenue sharing system that is not in accordance with the initial provisions. On the other hand, customers are still committing fraud by manipulating business ownership information and also not using the given capital as business capital.